Principal Management in Implementing the Deep Learning Approach to Improve Educational Quality at SMA Negeri 1 Penajam Paser Utara - Dinda Ruszayanthi; Masrur Yahya; Moh Bahzar; Widyatmike Gede Mulawarman; Usfandy Haryaka; Akhmad Akhmad (Cita konsultindo, 2026)
This study examines the principal's management in implementing the deep learning pedagogical approach to improve educational quality at SMA Negeri 1 Penajam Paser Utara. The research was motivated by the need to strengthen 21st-century competencies, character development, and meaningful learning in the context of Indonesia's Merdeka Belajar (Freedom to Learn) curriculum policy. Employing a qualitative case study design, data were collected through in-depth interviews, observation, and documentation analysis involving the school principal, vice principal for curriculum affairs, teachers, the school committee, and students. Data were analyzed using Miles and Huberman's interactive model: data reduction, data display, and conclusion drawing. The findings reveal that the principal's management in implementing deep learning was executed strategically across four management functions: (1) Planning the principal integrated deep learning principles into the School Operational Curriculum (KOS), lesson plans, and teacher professional development programs, with sensitivity to student diversity including student athletes; (2) Organizing collaboration was strengthened through internal subject teacher forums (MGMP), academic supervision, and a school quality assurance team, reflecting principles of distributed leadership; (3) Implementing learning shifted toward student-centered activities including project-based learning, contextual discussion, formative assessment, and reflective practice, enhancing student engagement and critical thinking; (4) Evaluating comprehensive and participatory evaluation involving teachers, students, and the school committee served as the basis for continuous improvement and evidence-based decision making. The study concludes that visionary, collaborative, and instructionally-focused principal leadership is the key determinant in successful deep learning implementation and educational quality improvement.